CXCL12 alone is enough to Reprogram Normal Fibroblasts into Cancer-Associated Fibroblasts - Zelong Ma; Diping Yu; Siqi Tan; Hao Li; Faxiao Zhou; Lei Qiu; Xiaoli Xie; Xiaoming Wu (Cell Death Discovery)
Abstract Cancer-associated fibroblasts (CAFs) are critical components of the tumor microenvironment (TME), playing significant roles in regulating cancer progression. However, the underlying mechanism of CAFs activation remains elusive. In this study, we aim to investigates the mechanisms by which CAFs promote the conversion of normal fibroblasts (NFs) to CAFs in lung cancer, with a focus on the role of p53 mutations and the CXCL12/STAT3 signaling axis. We found that CAFs significantly induced NFs to acquire CAFs properties (called CEFs), including upregulation of α-SMA and Vimentin, enhanced proliferation and migration, and increased ability to promote lung cancer cell migration. In vivo, CEFs accelerated A549 xenograft growth and induced spontaneous lung metastasis. CXCL12 was identified as a key factor in NFs-to-CEFs conversion, with its expression positively correlated with CAFs markers in lung cancer. Further investigation confirmed that CXCL12 is sufficient to reprogram NFs into CAFs through the STAT3 pathway. Notably, inhibiting CXCL12 signaling and the STAT3 pathway reduced the conversion of NFs to CAFs, thereby hindering lung cancer progression progression both in vitro and in vivo. Our study reveals CAFs could promote the conversion of NFs to CAFs-like cells through the CXCL12/STAT3 axis, enhancing tumor growth and metastasis in lung cancer. Therefore, inhibition of the CXCL12/STAT3 axis is a promising strategy for the treatment of lung cancers and other CXCL12‐dependent malignancies.